AMELIORATIVE POTENTIALS OF Trigonella foenum-graecum (FENUGREEK) SEEDS ON PROTEIN-ENERGY MALNOURISHED RATS - Sulyman, Rofiat A.; Ibrahim, Abdullah S. (FUDMA JOURNAL OF SCIENCES, 2024)
Malnutrition especially Protein-Energy Malnutrition (PEM) is one of the major challenges that brings about both short and long term health issues as well as weaken immune system and necrosis. It accounts for 45% of child deaths in both low and middle income countries. Trigonella foenum-graecum, a leguminous plant known for its antiviral, antimicrobial, anti-inflammatory and antioxidant was evaluated for its potential as diet supplement in the body of a protein-energy malnourished individual using wistar rats as a model. 74 female wistar rats weighing between 50 and 70g used for the study were malnourished by feeding them with low protein iso-caloric diet for 4 weeks. The rat samples were grouped namely as untreated group (malnourished rats that were not treated), commercial-fed group (malnourished rats treated with commercial feed), 25 g/kg, 50 g/kg and 100 g/kg supplemented diets groups (malnourished rats treated with 25 g/kg, 50 g/kg and 100 g/kg fenugreek seeds supplemented diets respectively) and were treated for 4 weeks after which they were sacrificed. The proximate analysis of the feeds were carried out, the anthropometric parameters, hematological parameters, total protein and lipid profile of the experimental animals were also assessed. There were significant (p0.05) difference in the observed parameters of malnourished rats when compared with the control which were reversed when treated with fenugreek seed supplemented diets. Hence, 25 g/kg, 50 g/kg and 100 g/kg fenugreek seed supplemented diets improves the nutritional status of malnourished rats.
Keywords: Malnutrition; Fenugreek; Hematology; Supplement diet